A case report of nilotinib-induced irreversible interstitial lung disease. Issue 4 (28th January 2022) - Cho, Jun Yeun; Lee, Ok-Jun; Kwon, Jihyun; Kim, Dohun; Shin, Yoon Mi
Abstract: Rationale: Nilotinib is a second line tyrosine kinase inhibitor to treat patients with chronic myeloid leukemia after imatinib resistance or intolerance. Drug related pulmonary complication is known to be rare. We discuss a case of nilotinib-induced interstitial lung disease presenting with nonspecific interstitial pneumonia on the unilateral lung. Patient concerns: A 46-year-old man with chronic-phase chronic myeloid leukemia presented with cough and weight loss for 2 months. He had been treated with nilotinib for 52 months. Diagnosis: Computed tomography scan showed right lung dominant consolidations, ground glass opacities and traction bronchiectasis. Bronchoalveolar lavage fluid analysis revealed no evidence of infection or malignancy. Surgical lung biopsy specimen was consistent with fibrosing nonspecific interstitial pneumonia. The patient was diagnosed with nilotinib induced interstitial lung disease. Interventions: Corticosteroid treatment was initiated with prednisolone (50 mg daily) and slowly tapered down for 2 months. Outcomes: Cough improved after the course of corticosteroid treatment. However, fibrotic lung lesions persisted. Reinitiation of nilotinib resulted in the worsening of lung lesions. Lessons: We report a case of irreversible interstitial lung disease that caused by nilotinib. Clinicians should have suspicion of this potential pulmonary complication in patients with respiratory symptoms and abnormal radiologic findings during nilotinib treatment, albeit rarely.